Shaping romance : interpretation, truth, and closure in twelfth-century French fictions - Bruckner, Matilda Tomaryn (University of Pennsylvania Press, 1993)
Examines a set of five twelfth-century romance texts--complete and fragmentary, canonical and now neglected, long and short--to map out the characteristics and boundaries of the genre in its formative period.
Keywords: Tristan -- (Legendary character) -- Romances -- History and criticism.; Tristan -- (Legendary character); French poetry -- To 1500 -- History and criticism.; Narrative poetry, French -- History and criticism.; Arthurian romances -- History and criticism.; Knights and knighthood in literature.; Romances -- History and criticism.; Fictions, Theory of.; Rhetoric, Medieval.; Closure (Rhetoric); Poésie française -- Jusqu'à 1500 -- Histoire et critique.; Cycle d'Arthur -- Histoire et critique.; Roman courtois -- Histoire et critique.; Théorie de la fiction.; Rhétorique médiévale.; Conclusion (Littérature); Poésie narrative française -- Histoire et critique.; POETRY -- Continental European.; LITERARY CRITICISM -- Medieval.; Arthurian romances; Fictions, Theory of; French poetry; Knights and knighthood in literature; Narrative poetry, French; Rhetoric, Medieval; Romances; Middeleeuwse romans (teksten); Frans.; To 1500; Criticism, interpretation, etc.